Ability of XP- Endo Finisher and XP-Endo Finisher-R in Removal of debris from the root canal walls after Retreatment: An In-Vitro Study - Mhd AGHIAD ALZUABI; Roula ABIAD (International Arab Journal of Dentistry (IAJD), 2020)
Objective: The aim of this study was to evaluate the ability of XP-Endo Finisher (XP-F) and XP-Endo Finisher–R (XP-FR) instruments in cleaning the root canal dentinal walls from filling debris.Methodology : Root canals of 24 extracted human mandibular premolars (N=24) were prepared with R3 I-Race files (30/.04) and filled with warm vertical compacted gutta-percha (GP) and root canal resin sealer (Adseal, Meta Biomed Co., LTd., Cheongju City, Chungbuk, Korea). Root canals were then retreated using D-Race files and shaped with BT-Race 35/.04. After that, teeth were divided into three groups according to the final methodof cleaning:  Group A: Final irrigation with NaOCl only, Group B:  Additional use of XP-Endo Finisher and Group C: Additional use XP-Endo Finisher-R. Teeth were rendered transparent for the evaluation of the residual GP/Sealer in Bucco-Lingual and mesial-distal directions. Statistical analysis was performed by using the statistical software SPSS 24.0 for Windows.Result:  All retreatment techniques used in this study left some filling material inside the root canal. Images in buccolingual and mesiodistal directions showed no significant differences between the groups (p>0.05).Conclusion: None of the finishers were able to completely remove the root canal filling material from root canal walls.